Tourism Marketing Strategy in Facing Tourism Challenges and Opportunities in Badung Regency, Bali - Ayu, Ni Luh Ayu Rai Saridarmini; Ni Nyoman Yuliastari; Ayu Sri Rachmayuni; Ida Ayu Dyana Prawerti; I Gusti Ngurah Putu Dedy Wirawan (Jurnal Internasional Riset Bisnis Pariwisata, 2023)
As the Heart of Bali Tourism, Badung Regency plays an important role in the development of Tourism in Bali Province. To ensure sustainable Badung Regency Tourism, real steps must be taken immediately to overcome the negative impacts caused by Tourism itself. The formulation of marketing strategies was obtained from the implementation of FGD (Focus Group Discussion), which was attended by tourism stakeholders and related agencies within the Badung Regency government. The data was analyzed using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The use of digital platforms, besides being considered effective and efficient in promoting tourist attractions in Badung Regency, can also be used as a medium to socialize Do's and Don'ts related to what tourists can and should not do during their visits in Badung Regency in particular and Bali Island in general, so that negative impacts and problems caused by the tourism sector can be minimized.  Good coordination and collaboration between tourism stakeholders and local governments are also important factors that must always be maintained, and are expected to be able to overcome problems that arise in the community due to the adverse effects of tourism. Badung Regency must continue to improve itself in improving the safety and comfort of tourists, so that it can strengthen its position as a Regency that dominates the favorite destination of domestic and foreign tourists visiting Bali Island.